Seedling establishment, biomass yield and water use efficiencies of four maize varieties as influenced by water deficit stress (2017)
Water stress is one of the major abiotic factors affecting crop growth and development at every growth stages. Effects of water deficit on the vegetative growth stage of four maize varieties consisting of two Quality Protein Maize varieties (ILE1OB and ART98SW6OB) and two drought tolerant checks (TZPBSR and DTESTRSYN) were evaluated under the screen house conditions at the Institute of Agricultural Research and Training (I.A.R & T), Moor Plantation, Ibadan. Maize seeds were sown in 20 L plastic pots filled with 15 kg top soil, which were subjected to four watering regimes of 25, 50, 75 and 100% field capacities (FC). The experimental design was a 4 x 4 factorial fitted into CRD with four replications. Data were collected on days to germination, number of leaves per plant, leaf area, plant height, stem diameter, leaf extension rate, biomass yield and water use efficiency. The result showed that days to germination were prolonged as the moisture availability decreases, while water use efficiency increased as the moisture level reduced. Reduction in moisture availability caused significant reduction in the other evaluated parameters. At 25% FC DTESTRSYN was superior in leaf area, number of leaves per plant, days to germination and water use efficiency, TZPBSR had highest values for stem diameter and biomass yield, while ILE1OB was superior in plant height, stem diameter, leaf and stem extension rate. ILE1OB competes favourably with the drought tolerant checks and performed better than ART98SW6OB. Adequate moisture condition is fundamental for normal growth and development in maize crops.